Optimized antibacterial measures against Escherichia coli O157:H7 and Staphylococcus aureus - Raftari, Mohammad; Jalilian, Farid Azizi; Abdulamir, Ahmed Sahib; Ghafurian, Sobhan; Radu, Son; Sekawi, Zamberi; Abu Bakar, Fatimah (Academic Journals, 2011)
Varied mixtures of different concentrations 1, 1.5 and 2% of acetic (AA), lactic (LA), propionic (PA) and formic (FA) acids at 1:1 ratio were spray-washed on inoculated meat to evaluate their efficacy in reducing loads of Escherichia coli O157:H7 andStaphylococcus aureus on meat tissue. It was found that increasing the concentration of the used organic acids increased the bacterial lethality proportionally. And significant difference (P<0.05) was observed in the lethal effect of different mixtures and concentrations of the used organic acids. As a novel combination, FA treatments as combinations with AA, LA, and PA, especially FA with LA, reduced bacterial loads greatly, up to 3 logs cfu/ml and eradicated inoculated bacteria, E. coli O157:H7 and S. aureuscompletely within 3-6 days. This reduction was higher than that incurred by other combinations. Significantly, higher log reductions by the used organic acids were obtained for S. aureus than for E. coli O157:H7. It was concluded that the combination of LA and FA treatment was a highly promising, feasible, and economical method of decontaminating meat surface from both E. coli O157:H7 and S. aureus bacteria. Moreover, it is safe if compared with other approaches.